2011
DOI: 10.3892/mmr.2011.515
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of CCL5 expression in classical Hodgkin's lymphoma L428 cell line

Abstract: Abstract. CCL5 is one of the chemoattractant cytokines involved in inflammatory observed in both diffuse large B-cell lymphoma (DLBCL) and classical Hodgkin's lymphoma (CHL). However, the pathological effects of CCL5 remain unclear. To gain a better understanding of the role of CCL5 in CHL and DLBCL, we examined the expression of CCL5 in the CHL cell line L428 and the DLBCL cell lines Ly1 and Ly8, as well as its chemotactic effect on CD4 + T cells. CCL5 mRNA expression was detected by real-time quantitative RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The T cells surrounding Reed-Sternberg cells express CCL5, which acts as a chemo-attractant for monocytes, eosinophils, basophils and mast cells as well as CD4 positive T cells ( 30 , 31 ). C-C chemokine receptor type 3 (CCR3) + Th2 cells and eosinophils are attracted by the CCL1(eotaxin) produced by fibroblasts surrounding RS cells ( 32 , 33 ).…”
Section: Chemokines and Cytokinesmentioning
confidence: 99%
“…The T cells surrounding Reed-Sternberg cells express CCL5, which acts as a chemo-attractant for monocytes, eosinophils, basophils and mast cells as well as CD4 positive T cells ( 30 , 31 ). C-C chemokine receptor type 3 (CCR3) + Th2 cells and eosinophils are attracted by the CCL1(eotaxin) produced by fibroblasts surrounding RS cells ( 32 , 33 ).…”
Section: Chemokines and Cytokinesmentioning
confidence: 99%
“…Several studies have been performed to investigate the expression of chemokine receptors and their ligands in the HRS cells of cHL [15,16,17,18,19,20] These studies found that the chemokine receptors CCR5, CXCR3, CXCR4, CXCR5 and CCR7 are expressed in the HRS cells of cHL in a significant number of cases [15,18,19]. Furthermore, the ligands CXCL10, CXCL12, CXCL13, CCL21, CX3CL1, CCL5 and CCL17 are expressed in cHL cell lines and primary HRS cells [17,18,19,21,22]. CCL17 and CCL5 are capable of attracting T helper 2 (Th2) and regulatory T (Treg) cells, which interact with HRS cells and form what has been named rosettes around them [17,23].…”
Section: Introductionmentioning
confidence: 99%